The commercial role of the people of Dhimma in the Zayani Central Maghrib during the 7th A.H/13th A.D century (Journal of the College of Basic Education, 2022)
This research paper deals with the study of the commercial role of the people of Dhimma in the zayani Central Maghrib during the 7th century A.H/13th century A.D, whereby, during this time central Maghrib received the people of Dhimma who immigraled from Andalusia, and who are Inlegraled public life and contributed to various areas of life, where the economic activities in the Central Maghreb during the Zayani era witnessed a great development during this century, which gave way to the the people of Dhimmis to participate in the these various activities that had been known in the region and worked in different and diverse fields of work, which reflected positively on their economic conditions as wellas their social conditions.In addition, the people of Dhimmis has a significant role in the trade relations between the Alzayanih country and surrounding countries especially the Christian countries emerging in the period. Also the religious tolerance, which was provided by the sultans of the sons of Zayan, and the treaties and conventions that concluded which Christian countries, as well as the geographical location and ports that are enjoyed by The region play an important role in the emergence of the commercial business of the people of Dhimmis, particularly at the level of foreign trade, which used to generate abundant profits.